‘One size does not fit all’: Engaging students who have experienced trauma - Parker, Rachel; Hodgson, David (Australian Institutes for Educational Research, 2020)
Responding to the social, relational and emotional needs of school students is now squarely within the purview of schools, teachers and school support staff. The everyday work of teachers may involve grappling with student disengagement, especially in regards to students who have experienced past trauma. It is a problem that presents ongoing challenges for educators and school policy-makers seeking to work out how to respond to student disengagement through social and emotional learning. This research aims to identify the skills and knowledge that are foundational to supporting and engaging students at educational risk in social and emotional learning. Using a phenomenographic research methodology, interviews were conducted with experienced teachers who specialise in the areas of engagement, behaviour and social-emotional learning. This research identified nine domains of engagement, and presents these as a conceptual framework that can guide where and how staff in schools can intervene with modifications that will positively impact students’ lives. The paper outlines a framework to help teachers and other school staff to plan and implement a responsive and dynamic approach to social and emotional learning, which can support improved immediate, short-term and long-term, health and well-being outcomes for students.